Rethinking sitting. - Opsvik, Peter, ....- (Oslo : Gaidaros, 2008)
In "Rethinking Sitting", the designer best known for the Tripp Trapp chair offers insight into his thinking about sitting and explains the philosophy that informs his pioneering chairs. Peter Opsvik designs beautiful seating that allows as many different sitting postures as possible and makes it easy to move and change frequently between them. "Rethinking Sitting" presents abundant drawings and photographic examples drawn from Opsvik's wide-ranging body of work along with text explaining his unconventional seating solutions. "Rethinking Sitting" contains useful information for everyone who, for professional, educational or personal reasons, is interested in sitting solutions-as all of us who live in a sedentary society should be.